Naturally occurring amino acid substitutions at Arg1174 in the human insulin receptor result in differential effects on receptor biosynthesis and hybrid formation, leading to discordant clinical phenotypes - Rau, H; Kocova, M; O'Rahilly, S; Whitehead, J P (American Diabetes Association, 2000)
Missense mutations in the tyrosine kinase domain of the human insulin receptor frequently result in a dominantly inherited form of insulin resistance. We noted a marked disparity in the clinical phenotypes of our study subjects with different missense mutations at the same residue (Arg1174) of the insulin receptor. Subjects with a tryptophan substitution (W) were only moderately hyperinsulinemic, whereas those with a glutamine substitution (Q) had severe clinical and biochemical insulin resistance. Studies were undertaken to explore the molecular mechanisms underlying these differences. Both W and Q mutant receptors bound insulin normally but were kinase inactive. The W mutation resulted in more rapid degradation of newly synthesized mutant receptor, which contrasted with the near-normal biosynthesis of the Q receptor. The propensity of the W receptor to form hybrids with the cotransfected wild-type (WT) receptor was also markedly impaired compared with the Q receptor, to an extent greater than could be explained by lower steady-state expression. Thus, the more clinically benign consequences of the heterozygous W mutant receptor are likely to relate to its impaired biosynthesis and/or reduced capacity to form hybrids with WT receptors. In addition to providing an explanation for the milder phenotype of 1174W versus 1174Q carriers, these studies provide further support for the notion that the dominant-negative effect of insulin receptor tyrosine kinase mutations involves the competition between inactive mutant homodimers and WT/mutant hybrids with active WT homodimers for both ligands and intracellular substrates.